How to research the behaviour of trading agents in a CDA environment. (17th December 2009) - Ilieva, Galina
During the last decade, there has been a huge increase in the volume of internet business transactions which in turn led to the emergence of a new field of scientific research – the so-called agent-based computational economics. This field is an intersection point of computer science and microeconomics. Software agents possess certain qualities and characteristics which enable them to effectively represent (and in some cases entirely replace) their owners in gathering and analysing relevant information and making decisions with whom, when and at what price to strike a deal. In order for them to be able to conduct efficient transactions, agents must have appropriate strategies for trading negotiations at their disposal. This paper is aimed at investigating the process of multi-agent negotiations by means of a continuous double auction (CDA) and presents one possible approach for finding an effective solution to the problem of resource allocation in a distributed computational environment.